Theological Influence or the Consequences of Defending Rights: a Survey of the Sources of Chinese Christian Ideas of Rights - ZHANG, Zhipeng (Journal of Research for Christianity in China (JRCC), 2025)
Based on a small scale of questionnaire survey, this paper found that compared with all the respondents, Chinese Christian believers have a stronger sense of rights, and their evaluation of the current rule of law is more severe. Further analysis shows that it is unregistered church members among Christian believers and those who have been violated are the firm supporters of modern rights and the rule of law. The two groups often intersect because most unregistered churches experience different forms of infringement. From the perspective of the historical origin and internal mechanism of Chinese Christianity, the content of modern rule of law and concept of rights have long been absent in the theological construction, with only some abstract theological principles and justice evaluation based on individual religious feelings. At present, what really drives Chinese christians to have the modern concept of rights and the thinking of rule of law is the various events that they encounter in the reality, which involve the protection of rights. These christians who have mastered the modern concept of rule of law and rights further integrate relevant contents into the church theology, so that the churches begin to develop in different ways in terms of theological cognition.